Export-Led Growth Hypothesis: Further Econometric Evidence From South Asia (2005) - Shirazi, Nasim Shah; Turkhan Ali , Abdul Manap (John Wiley & Sons, Inc, 2005)
This paper examines the export-led growth (ELG) hypothesis for five South Asian countries through cointegration and multivariate Granger causality tests. Strong support for a long-run relationship among exports, imports, and real output for all the countries except Sri Lanka were found. Feedback effects between exports and GDP for Bangladesh and Nepal and unidirectional causality from exports to output in the case of Pakistan were found. No causality between these variables was found for Sri Lanka and India, although for India GDP and exports did induce imports. A feedback effect between imports and GDP was also documented for Pakistan, Bangladesh, and Nepal, as well as unidirectional causality from imports to output growth for Sri Lanka. These and other findings are discussed from the standpoint of the export-led growth hypothesis.